Ответ(ы) на вопрос:
1). 9/16 - х = 1/2 (1/2 = 8/16)
х = 9/16 - 8/16
х = 1/16
2). х + 2/3 = 7/8 (7/8 = 21/24; 2/3 = 16/24)
х = 21/24 - 16/24
х = 5/24
3). 1/2 + х = 23/24 (1/2 = 12/24)
х = 23/24 - 12/24
х = 11/24
4). х - 3/8 = 1/4 (1/4 = 2/8)
х =3/8 + 2/8
х = 5/8
1) =
-х=1/2-9/16=(1*8)/(2*8)-(9*1)/(16*1)=8/16-9/16=(8-9)/16
-х=-1/16
х=-1/16:(-1)
х=1/16
3)=
х=23/24-1/2=23/24-(1*12)/(2*12)=23/24-12/24=(23-12)/24
х=11/24
2)=
х=7/8-2/3=(7*3)/(8*3) - (2*8)/(3*8)=21/24-16/24=(21-16)/24
х=5/24
4)=
х=1/4+3/8=(1*2)/(4*2)+3/8=2/8+3/8=(2+3)/8
х=5/8
Не нашли ответ?
Похожие вопросы